2015
DOI: 10.3109/19396368.2015.1085605
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase in diabetic rat testicular tissue and the effects of pentoxifylline therapy

Abstract: Diabetes is known to be associated with erectile dysfunction, retrograde ejaculation, level of testicular hormone, and a decrease in semen quality, respectively. In this project, we aimed to investigate at the molecular level, the effects of NOS on testes pathology in diabetes and examine the effects of pentoxifylline on healing. A total of 50 Wistar albino male rats were divided into five groups: Group I control; Group II only diabetes; Group III and IV diabetes + pentoxifylline; Group V only pentoxifylline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Consistent with a previous report [50], the penile cross-sectional area (%) was decreased in DM mice, resulting in atrophy of the penis. The increase of collagen fibers in the testis of animals with DM 72 Day A may have been caused by increased expression of transforming growth factor beta 1 and nitric oxide synthase [51][52][53][54]. Similar to our study, previous studies have demonstrated decreases of sperm concentration in DM human and animal models [5,6,37,42,[55][56][57][58], which may be due to impaired spermatogenesis [5,6,12,57,[59][60][61].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with a previous report [50], the penile cross-sectional area (%) was decreased in DM mice, resulting in atrophy of the penis. The increase of collagen fibers in the testis of animals with DM 72 Day A may have been caused by increased expression of transforming growth factor beta 1 and nitric oxide synthase [51][52][53][54]. Similar to our study, previous studies have demonstrated decreases of sperm concentration in DM human and animal models [5,6,37,42,[55][56][57][58], which may be due to impaired spermatogenesis [5,6,12,57,[59][60][61].…”
Section: Discussionsupporting
confidence: 85%
“…The T2DM mice received an HFD (60 kcal% fat, D12492, Research Diet) for 14 consecutive days and were then induced with a single dose of STZ of 85 mg/kg BW [20,21] followed by continuous feeding with an HFD as previously described [26][27][28]. On days 3,6,12,18,24,30,36,42,48,54,60,66, and 72, the mice in both DM groups were assessed for actual DM induction using a blood glucose oxidase reaction monitoring system with blood from a tail prick. Mice were considered to have DM when their blood glucose levels were greater than 250 mg/dL.…”
Section: Animals and Induction Of Diabetesmentioning
confidence: 99%
“…Nitric oxide (NO) is a small, lipophilic molecule that easily passes through membranes. In normal physiological conditions, NO is a free radical molecule with a lifetime of a few seconds which is synthesised by nitric oxide synthase (NOS) (Sonmez et al, ). iNOS, one of the three isoforms of nitric oxide, is associated with spermatogenesis, infertility, sperm maturation, and Sertoli and germ cell apoptosis in the testis (Costur et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was obtained to quantify protein concentration with the Bicinchoninic Acid Total Protein Quantification Kit. Western blot analysis was performed as described (Sönmez et al 2016;Liu et al 2017). The protein samples (30 μg) were run on 10% SDS-PAGE, transferred on polyvinylidenedifluoride (PVDF) membranes (Millipore, USA).…”
Section: Western Blotmentioning
confidence: 99%